Relationship between High Sensitivity C-Reactive Protein Levels and the Severity of Vulgaris Psoriasis - William Halomoan Francisco Purba; Kristo Alberto Nababan; Deryne Anggia Paramita (Indonesian Journal of Global Health Research, 2026)
Psoriasis vulgaris is a chronic immune-mediated inflammatory skin disease increasingly recognized as a systemic inflammatory condition. High-sensitivity C-reactive protein (hs-CRP) is a sensitive marker of systemic inflammation, but its relationship with psoriasis severity remains inconsistent. This research evaluate the association between serum hs-CRP levels and disease severity in patients with psoriasis vulgaris. To evaluate the association between serum hs-CRP levels and disease severity in patients with psoriasis vulgaris. A cross-sectional analytical study was conducted involving 30 patients with psoriasis vulgaris and 30 control subjects at a tertiary hospital in Indonesia. Samples were obtained using non-probability sampling with a consecutive sampling technique, in which subjects who met the inclusion criteria were recruited sequentially until the minimum required sample size was achieved. Psoriasis severity was assessed using the Psoriasis Area and Severity Index (PASI). Serum hs-CRP levels were measured using enzyme-linked immunosorbent assay. Correlations between hs-CRP levels and PASI scores were analyzed using Spearman’s rank test. Most psoriasis patients had mild disease (56.7%). The mean serum hs-CRP level in the psoriasis group was 1.23 mg/L. No significant correlation was found between hs-CRP levels and PASI scores (r = 0.128, p = 0.499) or categorical disease severity. Although hs-CRP levels were higher in psoriasis patients than controls, the difference was not statistically significant. Serum hs-CRP levels were not associated with clinical severity of psoriasis vulgaris, suggesting that hs-CRP reflects systemic inflammation rather than cutaneous disease severity alone.